Triple Helix Sebagai Model Bagi Inovasi Pendidikan Tinggi: Analisis Logika Kelembagaan Dalam Pengembangan Kewirausahaan Dan Ekonomi - Aan Jaelani (UIN Siber Syekh Nurjati Cirebon, 2019)
AbstrakArtikel ini akan memaparkan tentang transformasi pendidikan tinggi yang mengalami perluasanm isi untuk memasukkan pembangunan ekonomi dan sosial serta kompetensi, reproduksi budaya dan penelitian dan pergeseran dari individu ke fokus organisasi. Dalam hal ini, model triple helix menegaskan hubungan antara universitas, industri, dan pemerintah sebagai strategi pengembangan untuk memenuhi modal sosialdankesenjanganteknologi, sehingga model iniinidapatmemberikankondisi yang optimal untukinovasiperguruantinggi. Dengananalisisteoriinstitusional yang memilikiempattahappengembangandalam proses pelembagaan model tersebut, makadapatdipahamibahwapolapraktik material yang dibangunsecarasosial, historis, asumsi, nilai-nilai, kepercayaan, danaturan-aturan yang dengannyaindividumenghasilkandanmereproduksisubsistensi material mereka, mengaturwaktudanruang, danmemberikanmaknapadarealitassosialmereka.Artikelinimenyimpulkanbahwalogikakelembagaan yang diharapkandapatbekerjameliputikepercayaandalaminovasisainsdanteknologisebagaikunciuntukpertumbuhankesejahteraanekonomi, orientasipasardalamkelulusanakademiktanpameninggalkanbudayalokal, peningkatandanperlindunganhakkekayaanintelektualdalamindustri, dankemampuanlembagadalampersainganpasar. Kata Kunci: pendidikantinggi, triple helix, logikakelembagaan, kewirausahaan THE TRIPLE HELIX AS A MODEL FOR INNOVATION OF HIGHER EDUCATION:Analysis of Institutional Logic in Entrepreneurship and Economic Development AbstractThis article will describe the transformation of higher education which is undergoing an expanded mission to include economic and social development as well as competence, cultural reproduction, and research and the shift from the individual to the organizational focus. In this case, the triple helix model emphasizes the relationship between universities, industry, and government as a development strategy to meet social capital and technological gaps, so that this model can provide optimal conditions for university innovation. By analyzing the institutional theory that has four stages of development in the process of institutionalizing the model, it can be understood that the pattern of material practices that are built socially, historically, assumptions, values, beliefs and rules by which individuals produce and reproduce their material subsistence, managing time and space, and giving meaning to their social reality. This article concludes that the institutional logic that is expected to work includes trust in scientific and technological innovation as a key to growing economic prosperity, market orientation in academic graduation without leaving local culture, enhancing and protecting intellectual property rights in the industry, and the ability of institutions in market competition. Keywords: higher education, triple helix, institutional logic, entrepreneurship